Watermarking digital images for copyright protection - BOLAND, FRANCIS MORGAN (IEE, 1996)
A watermark is an invisible mark placed on an image that is designed to identify both the source of an image as well as its intended recipient. The authors present an overview of watermarking techniques and demonstrate a solution to one of the key problems in image watermarking, namely how to hide robust invisible labels inside grey scale or colour digital images
PUBLISHED
Keywords: Copyright protection; Image processing; Steganography; Spread spectrum communications